The Translation Strategies of Idioms in J.K. Rowling’s Harry Potter and the Half-Blood Prince into Harry Potter dan Pangeran Berdarah-Campuran - Margarete Theda Kalyca Krisandini; Adi Sutrisno (Universitas Gadjah Mada, 2021)
Idiom is a fixed group of words which has a particular meaning. Translating idioms to another language can be considered complicated and quite challenging because it cannot be translated word-by-word. This research aims to identify the types of idiom found in the novel Harry Potter and the Half-Blood Prince and its translation strategies in Harry Potter dan Pangeran Berdarah-Campuran. The data used in the research were idioms found in Harry Potter and the Half-Blood Prince and idioms translation in Harry Potter dan Pangeran Berdarah-Campuran. The result shows that there are 270 idioms found in the novel. These idioms were classified into three types according to Chitra Fernando (1996). Most of the idioms belong to pure idiom with 137 idioms (50.9%), followed by semi idiom with 72 idioms (26.4%), and literal idiom with 61 idioms (22.7%). Furthermore, the translation strategies of these idioms were analyzed using the theory of idiom translation strategies by Mona Baker (1992) and Peter Newmark (1991). The most frequently applied strategy is translation by paraphrase with 222 idioms (82.2%), followed by literal translation with 28 idioms (10.4%), translation by using an idiom of similar meaning and dissimilar form of 14 idioms (5.2%), and finally translation by omission of 4 idioms (1.5%). Translation by paraphrase is the most frequently applied strategy because of the difficulty in finding equal idioms in target text.